Prevalence and Prognosis of Familial Hypercholesterolemia in Acute Coronary Syndromes Patients - Cordero, Alberto; M, Rosa; Lidón; Castro, Almudena; Fácila, Lorenzo; Nuñez, Julio; Mostaza, José; González-Juanatey, José Ramón (Cardiology and Cardiovascular Medicine, 2020)
Background: Familiar hypercholesterolemia (FH) is genetic disease that leads to increased serum low-density lipoprotein cholesterol (LDLc) and premature acute coronary syndromes (ACS). The objective of our study was describing the prevalence and prognosis of FH, assessed by Dutch Lipid Clinic Network (DLCN) criteria, in patients with ACS. Methods: We designed a multicentre, observational, prospective and nationwide registry of ACS patients admitted in 30 hospitals. The DLCN criteria were analysed in all patients and they were classified in:unlikely-FH (0-2 criteria), possible-FH (3-5 criteria), probable-FH (6-7 criteria) or definite-FH (>7 criteria). Premature ACS was defined if age at admission was <55 in men or <65. Results: we included 868 patients, 72.3% males and 20.6% diabetics. Unlikely-FH accounted for 84.2% of the cohort; the prevalence of possible FH was 14.5%, probable-FH 1.1% and only 1 patient had definite-FH. The prevalence of possible or probable FH increased up to 21% in patients with premature ACS. Patients with possible/probable FH had lower mean age but more peripheral arterial disease; also, had been diagnosed more often of hypercholesterolemia and had higher LDLc and statins treatments before admission. A progressive increase in the incidence of major cardiovascular events (MACE) was observed by each increase in one DLCN criteria (OR= 1.23 95% CI 1.08-1.39) or, globally, in patients with possible/probable FH (OR: 2.31 95% CI 1.35-3.96). Conclusions: 15.8% of patients with ACS have possible/probable FH and the prevalence increases up to 24% in patients with premature ACS. Patients with possible/probable FH have higher risk of in-hospital MACE.